Hydrogen gas sensing using palladium-coated microdisk microresonators - (:unkn) unknown (SPIE-INT SOC OPTICAL ENGINEERING, 2015)
An SU-8 polymer microdisk resonator coated with a palladium (Pd) layer and coupled to a single-mode optical waveguide is used to as a hydrogen (H-2) gas sensor. In the presence of H2 a red shift is observed in the spectral positions of the microdisk whispering gallery modes (WGMs) due to the expansion in the Pd lattice. H-2 concentrations below the flammable limit (4%) down to 0.3% could be detected in nitrogen atmosphere at room temperature. For H-2 concentrations between 0.3 1%, WGM spectral positions shifted linearly with H-2 concentration at a rate of 32 pm/%H-2. Average response time of the devices was measured to be 50 s for 1% H-2. The proposed device concept can also be used to detect different chemical gases by using appropriate sensing layers.
Keywords: Microdisk resonator; SU-8 polymer; hydrogen sensing; waveguide coupling; SENSORS